USING VISUAL MATERIALS TO IMPROVE SPEAKING AND LISTENING SKILLS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This thesis is about visual materials and qualities to develop speaking and listening skills in English. Also, there is given some information about importance of vizualization.